Intention to Use Internet of Things Among Future Accountants: Analysis Using the Technology Acceptance Model - Jasmani, Nurul Syamila; Shuhidan, Shazalina Mohamed; Awang, Yunita (Advances in Social Sciences Research Journal, 2024)
The study explores factors influencing future accountants’ intention to use the Internet of Things (IoT) in accounting by employing the Technology Acceptance Model (TAM). Key factors such as perceived ease of use, perceived usefulness, and attitude were examined using an online survey targeted to final-semester students at a public university’s Accounting Department. While 337 participants were targeted, only 121 took part. The primary objective of the survey is to access these students’ perceptions of the various factors that influence the integration of IoT into accounting practices. The data was analysed using statistical techniques include correlation analysis and regression to test multiple hypotheses about the relationships between factors. The study was able to provide insights into how IoT adoption among future accountants can help transform the accounting industry. It also enhances understanding on the challenges and opportunities in integrating IoT into accounting practices. Key findings indicate that perceived usefulness has a significant and positive relationship with behavioural intention among future accountants, suggesting that they are more inclined to adopt IoT if they perceive it as useful. However, perceived ease of use and attitude do not have statistically significant impact on behavioural intention. The findings can help educational institutions and technology providers better prepare accountants for an evolving job market.